Passive flow control in the wake of bed-mounted cylinders: a review and new experimental insights - Zia Ud Din Taj; Sabal Bista; Ram Balachandar (Frontiers in Mechanical Engineering)
Controlling wake flow behind bed-mounted circular cylinders is required in many engineering applications. This study investigates several passive flow control mechanisms, including the use of helical strakes, meshes, foam coverings, slots, and holes. A detailed review of existing experimental and numerical studies is conducted to examine the principles, applications, and effects of each method. While extensive research exists on individual flow control techniques, comparative studies between different methods are notably lacking. Additionally, variations in approach flow conditions across studies highlight the need for a systematic evaluation under identical or near-identical inflow conditions. To address these gaps, particle image velocimetry measurements were employed to capture and compare unsteady flow dynamics in the wake of various types of bed-mounted circular cylinders. Experiments were conducted at Reynolds number of 1.45×104, based on the cylinder diameter. The results show that the plain cylinder’s wake flow is dominated by a large recirculation region and downstream bifurcation, while the meshed cylinder shows minimal deviation from these characteristics. The cylinders with holes generate localized turbulence and spiraling flow patterns, with diminishing effects downstream. The helical strakes induce unique channelized flow and sustained turbulence downstream, whereas the single and cross-slotted cylinders enhance near-wake turbulence and velocity via high-velocity jets, particularly in the cross-slotted configuration, making it ideal for heat transfer applications. In contrast, foam-covered cylinders effectively reduce turbulence and flow fluctuations, offering potential for applications requiring flow stability and drag reduction.